1971
DOI: 10.1111/j.1537-2995.1971.tb04367.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Hemagglutination Inhibition Studies of Blood‐group Substances

Abstract: Quantitative hemagglutination inhibition studies of the pre‐ and postimmune sera of nine human volunteers immunized with hog A substance have confirmed earlier findings that the character of the agglutinins is altered by immunization. Concomitant with immune antihog A antibody production, the slope of the probit‐log hemagglutination inhibition assay curve became steeper, the amount of hog A substance required to inhibit the agglutinins became smaller, and the rate of dissociation of hog‐A‐anti‐A complexes beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1976
1976

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…GIBBS et al [14] have demonstrated that a mixture of anti-A, A substance and A red cells resulted in a state of equilibrium between the three components since the strength of the agglutination was the same irrespective of the order in which the components were added. Thus, it would appear that the blood group substance exerts its main protective effect by competing with the red cells for available antibody and not by coating the sensitised cells as suggested by the studies of VOS and KIRK [44].…”
Section: Discussionmentioning
confidence: 99%
“…GIBBS et al [14] have demonstrated that a mixture of anti-A, A substance and A red cells resulted in a state of equilibrium between the three components since the strength of the agglutination was the same irrespective of the order in which the components were added. Thus, it would appear that the blood group substance exerts its main protective effect by competing with the red cells for available antibody and not by coating the sensitised cells as suggested by the studies of VOS and KIRK [44].…”
Section: Discussionmentioning
confidence: 99%